Design of monitoring and protection system for converter - Peh, Jun Xiang (2017)
This report will comprise of literature review of why inverter such as Cascaded HBridge (CHB) was chosen over Neutral Point Clamped (NPC) and Flying Capacitor (FC) with the help of experiment. Using EtherCAT, it has improved enhanced system capability, easy to use and convenient. The capabilities of synchronization and full transmission usage are good for application like motion where large amount of drives are needed to synchronize. It helps to save installation cost by getting rid of the Ethernet start topology and all routers switches. The project will be using Ethernet cable to connect between microcontroller and a computer with TwinCAT software. The microcontroller will act as a slave and the computer will act as a master. The computer will be controlling the inputs and outputs of the microcontroller and it can get the temperature reading. In addition, Graphical User Interface (GUI) will be created and integrated with TwinCAT for human-beings to understand.